Infection-associated hemophagocytic syndrome complicated by infectious lymphoproliferation: a case report - Syrůcková, Z; Starý, J; Sedlácek, P; Smísek, P; Vavrinec, J; Komrska, V; Roubalová, K; Vandasová, J; Sintáková, B; Housková, J; Hassan, M (Pediatric hematology and oncology, 1996)
The case of a 7-year-old boy with virus-associated hemophagocytic syndrome (VAHS) and serologically proven parvovirus B-19 infection is described. The patient with VAHS presented with fever, hepatosplenomegaly, pancytopenia, and hyperlipidemia type IV. After induction therapy with VP-16 and prednisone, partial remission was achieved. Despite maintenance therapy, reinductions, and the addition of cyclosporine A for 3 months, several relapses occurred. The therapy was stopped because of life-threatening complications (Klebsiella sepsis, neutropenic enterocolitis, and stercoral peritonitis). The complications were treated successfully. The patient status was stabilized after splenectomy. However, hepatomegaly progressed slowly and the hyperlipidemia endured. Ten months after the diagnosis leukocytosis with absolute T lymphocytosis appeared. Reactivation of VAHS was suspected and intravenous immunoglobin and then antilymphocyte immunoglobulin ALG therapy were started. The resultant decrease in leukocytosis was prompt, but lymphopenia did not occur. Virostatic treatment with foscarnet was introduced based on human herpesvirus-6 seroconversion. Twenty-six months after the diagnosis, the patient is well, without any sign of VAHS or lymphoproliferation.
Keywords: lidský parvovirus B19; Drug Administration Schedule; mužské pohlaví; kostní dřeň; Histiocytosis, Non-Langerhans-Cell; dítě; slezina; Child; Humans; Lymphoproliferative Disorders; histiocytóza z non-Langerhansových buněk; Herpesvirus 6, Human; rozvrh dávkování léků; lymfoproliferativní nemoci; Bone Marrow; Spleen; lidský herpesvirus 6; Parvovirus B19, Human; lidé; Male